GREBEG PANCASILA VALUES AS SOURCES OF LEARNING SOCIAL STUDIES - Katon Galih Setyawan; Nasution; Muhammad Ilyas Marzuqi (Jurnal Partisipatoris, 2021)
That in delivering the material, the teacher still uses conventional methods. The teacher is more dominant in delivering the material and students only take notes. Most teachers are more oriented towards understanding and mastering material based on textbooks without relating existing phenomena. For example, when explaining about culture, only a general description is given. Therefore, to be able to fulfill the initial goals of social studies education, it can be done through fun learning that is close to the scope of students' lives. The surrounding environment can be used as a tool as a source of social studies learning so that the explanation of the material does not only refer to the explanations in the textbook but can also help students get to know the surrounding environment better. This can be done through learning based on the cultural capital of the local community. One of the objectives of this research is to develop a learning resource instrument based on the cultural capital of the Grebeg Pancasila ceremony for junior high school social studies lessons. The theoretical studies used are junior high school social studies learning, cultural capital, learning resources and the Pancasila Grebeg. The method used is descriptive qualitative and takes the research location in Blitar City with the research subject being culturalists/historians, Head of the Department of Tourism and Culture and social studies teacher at Blitar City Junior High School. The results of the study show that there are several values in the Pancasila Grebeg program that are in accordance with the study materials or materials in social studies learning in junior high schools, namely social integration, mutual cooperation and a sense of nationalism. These materials are part of Basic Competence 3.2, mainly studied in class VIII semester 1.